Transnational Europe Promise, Paradox, Limits - DeBardeleben, J.; Hurrelmann, A.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2011)
Transnational connections are a defining feature of contemporary Europe. They include cross-border economic and cultural exchange, migration, and political activism. This volume probes their political and social significance and makes a case for incorporating transnationalism more systematically into the research agenda of European Studies.
Keywords: European Union; International relations; Sociology; Political science; Comparative politics; Globalization; European Union Politics; International Relations; Sociology, general; Political Science; Comparative Politics; Globalization